Determinant Accounting Information Systems (AIS) Quality and the Quality of Financial Reports: An Analysis of Good Corporate Governance (GCG) - Annisa Fitri Anggraeni; Nursepsanti Nursepsanti (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
This study aims to examine the influence of Good Corporate Governance (GCG) on the Quality of Accounting Information Systems (AIS), the influence of the Quality of Accounting Information Systems (AIS) on the Quality of Financial Statements, and the direct influence of Good Corporate Governance (GCG) on the Quality of Financial Statements within the Bandung City Government. A quantitative method with a descriptive-verificative approach was applied. Data were collected through questionnaires distributed to 126 employees from work units responsible for financial management and information systems at the Regional Secretariat of Bandung City Government. Data analysis employed the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique using SmartPLS to test the relationships among variables. The findings reveal that Good Corporate Governance (GCG) has a positive and significant effect on the Quality of Accounting Information Systems (AIS) with a path coefficient of 0.921 (t=53.43, p<0.05), and the Quality of Accounting Information Systems (AIS) has a positive and significant effect on the Quality of Financial Statements with a path coefficient of 0.658 (t=4.743, p<0.05). However, Good Corporate Governance (GCG) does not have a significant direct effect on the Quality of Financial Statements (path coefficient=0.247, p=0.109), indicating that the relationship may be influenced by external factors such as audit quality, human resource competence, and organizational characteristics. In conclusion, enhancing the quality of financial statements is more effectively achieved through strengthening the quality of Accounting Information Systems (AIS), which serves as a mediating variable between GCG and the Quality of Financial Statements.